Activity and Stability of (Pr1-xNdx)2NiO4 as Cathodes for Solid Oxide Fuel Cells: Part V. In Situ Studies of Phase Evolution. Issue 12 (1st January 2017) - Dogdibegovic, Emir; Alabri, Nawf S.; Wright, Christopher J.; Hardy, John S.; Coyle, Christopher A.; Horlick, Samuel A.; Guan, Wanbing; Stevenson, Jeffry W.; Zhou, Xiao-Dong
Abstract : This study is to complement an early report (the manuscript is attached for review purpose) on the role of interlayer on activity and performance stability in praseodymium nickelates. The aforementioned report showed a remarkable 48% increase in power density while switching from common GDC interlayer to a new interlayer chemistry (PGCO). Furthermore, a stable long-term performance was linked with suppressed reaction between the cathode and PGCO interlayer. In this article, we report in situ studies of the phase evolution. The high energy XRD studies at a synchrotron source showed fully suppressed phase transition in praseodymium nickelates with PGCO interlayer, while the electrodes on the GDC interlayer undergo substantial phase transformation. Furthermore, in operando and post-test XRD analyses shown fully suppressed structural changes in electrodes operated in full cells at 750°C and 0.80 V for 500 hours. SEM-EDS analysis showed that the formation of PrOx at the cathode-interlayer interface may play a role in a decrease of mechanical integrity of the interfaces, due to thermal expansion mismatch, leading to a local stress between the two phases. Consequently, phase evolution at a narrow interface may propagate toward the electrode bulk, leading to structural changes and performance degradation.